2020
DOI: 10.1002/cpe.6076
|View full text |Cite
|
Sign up to set email alerts
|

Stock movement prediction with sentiment analysis based on deep learning networks

Abstract: With the development of Internet and big data, it is more convenient for investors to share opinions or have a discuss with others via the web, which creates massive unstructured data. These data reflect investors' emotions and their investment intentions, and it will further affect the movement of the stock market. Although researchers have been attempted to use sentiment information to predict the market, the sentiment features used are driven by outdated emotion extraction systems. In this article, we propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Recent works have demonstrated that taking into account external information, mainly provided in the form of sentiment regarding various financial assets [8,9,26,36], can significantly boost the performance of trading agents. At the same time, the development of powerful large-scale language models that can be trained on large collections of text documents, such as BERT [11] and roBERTA [6,7,16], which can be finedtuned on various tasks, such as sentiment analysis, provided additional powerful tools for automating sentiment extraction from online sources.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent works have demonstrated that taking into account external information, mainly provided in the form of sentiment regarding various financial assets [8,9,26,36], can significantly boost the performance of trading agents. At the same time, the development of powerful large-scale language models that can be trained on large collections of text documents, such as BERT [11] and roBERTA [6,7,16], which can be finedtuned on various tasks, such as sentiment analysis, provided additional powerful tools for automating sentiment extraction from online sources.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, the development of powerful large-scale language models that can be trained on large collections of text documents, such as BERT [11] and roBERTA [6,7,16], which can be finedtuned on various tasks, such as sentiment analysis, provided additional powerful tools for automating sentiment extraction from online sources. Indeed, it has been demonstrated that such information can be very useful for developing trading agents [23,26]. However, these approaches typically ignore that generic sentiment extractors, even when trained on large document collections, face significant challenges when used in domain-specific areas, such as finance [4].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Online financial news and other news articles are crucial tools for making many decisions, which may be used in a variety of research areas through sentiment analysis. A novel sentiment analysis system based on a deep neural network was developed in (Shi et al 2021 ). The novel technique improved sentiment categorization by 9% when compared to the logistic regression method.…”
Section: Related Workmentioning
confidence: 99%
“…Similar results were achieved in [ 16 ], where the application of text-mining technology to quantify the unstructured data containing social media views on stock-related news into sentiment scores increased the performance of the logistic regression algorithm. A more sophisticated approach that employs deep sentiment analysis was used to improve the performance of an SVM-based method in [ 17 ], indicating once again that sentiment features have a beneficial effect on the prediction.…”
Section: Related Workmentioning
confidence: 99%